Sosialisasi Standar Mutu Pendidikan: Implementasi Standar Mutu Global pada Satuan Pendidikan di Lingkungan Yayasan Adzkia Damiri Kabupaten Sukabumi - Lastriyani, Indri; Lidiawati; Warta, Waska; Wasliman, Iim (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2023)
In the world of education, the National Education Standards (SNP) act as the main guide that directs and guarantees the quality of learning across the country. learning across the country. More than just a set of rules, the SNP are important milestones that guide schools and educators to create effective and high-quality effective and high-quality learning processes. Quality Standards Education Quality Standards are the cornerstone that underpins the education system to achieve equality and sustainability. Schools that successfully meet these standards are considered as quality institutions, capable of upholding their educational programs in line with the SNP standards that are the minimum reference in managing programs in line with the SNP standards, which are the minimum reference in managing education in various regions. However, the next phase becomes increasingly crucial: improving quality by adopting international standards. Schools that have reached and exceeded the SNP standards are now going further. They no longer satisfied with just meeting national requirements, but are looking globally. global. Several schools under the Adzkia Damiri Foundation in Sukabumi District are exemplary. Sukabumi district are exemplary. For example, the Adzkia Integrated Islamic School (SIT) Sukabumi not only upholds national standards. They also carry out mission to be a model in shaping the character of young generations who are smart, creative, and broad-minded. smart, creative, and insightful and able to become agents of change in society. SIT Adzkia Sukabumi not only upholds national standards, but also adopts international management standards, enriching the quality of their education to a higher level. This service activity aims to educate the managers of Education units in Adzkia Education environment related to management quality standards with international standards that can be applied in the world of education, namely the applied in the world of education, namely the quality standard in question is ISO 21001.